An Examination of International Humanitarian Law of Armed Conflict: Perspective from the Legal Issues on War Crimes in Africa - NWALA Paul (International Studies Journal)
The practice of law of war has its modern origin from international laws of armed conflict which vehemently prescribes laws governing resort to force and also seeks to regulate the conduct of hostilities. Its extension to the protection of innocent civilians against their killings and subjection to inhuman or degrading treatments is of paramount to this study against the backdrop of violation of such provisions by war criminals, led to the birth of international humanitarian law. Therefore, this article seeks to examine relevant cases of war crimes in Africa and its legal implications. The study argues that international humanitarian law on armed conflict governs the treatment of prisoners of war, civilians in occupied territory, the sick and the wounded personnel, prohibits inhuman methods of warfare and protection of human rights in situation of armed conflict (war). Furthermore, the study posits that any violations of these prescribed rules in the conduct of armed conflict simply known as war, invariably constitutes war crime and that offenders should not go unpunished. The paper made use of archival materials, historical analysis and review of related literature documents to address the issue of international humanitarian laws on armed conflict as it should be sustained. This study concludes that there should be adequate unilateral and collective security and sanctionable measures by the United Nationssufficient enough to protect innocent civilians, basic survival infrastructures, surrendered combatants, prisoners of war during armed conflict and that any warlord(s) who must have acted in contrary to the law of war as was codified at the Hague Conference of 1889 and 1907 as well as in fundamental breach of international law should be prosecuted accordingly by the International Criminal Court.